Financial Sector Assessment : Moldova - World Bank (Washington, DC, 2013)
The Financial Sector Assessment Program (FSAP) team produced an Aide Memoire and the following three detailed reports that were reviewed by and delivered to the authorities: 1) technical notes; 2) assessment of compliance with standards and codes; and 3) detailed bank-by-bank stress tests. The Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) section of the report was based on the report of an International Monetary Fund (IMF) technical assistance mission undertaken in April 2004. Although Moldova is the poorest country in Europe, measured by per capita Gross Domestic Product (GDP), the country has achieved some success in building up the framework of a functioning market economy, especially in the banking sector. In addition to the underlying structural weaknesses, there are several potential macroeconomic problems that increase the vulnerability of the financial system. These include: a) the direct financing of the state budget by the central bank against the background of the weak fiscal and external situation; b) dependency on remittances; and c) dollarization, in combination with significant exchange rate volatility.